Using the somatic cell count report - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1996)
High-producing dairy herds can consistently average a somatic cell count (SCC) <200,000. Herds with consistently higher averages can decrease SCC and realize higher profits. The SCC report discloses the pitfalls that need to be addressed before improvement can be made.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Somatic cell count